Clinical teacher education : reflections from an urban professional development school network - Bohan, Chara Haeussler; Many, Joyce (Readings in educational thought, 2011)
Clinical Teacher Education focuses on how to build a school-university partnership network for clinical teacher education in urban school systems serving culturally and linguistically diverse populations. The labor intensive nature of professional development school work has resulted in research institutions being slow to fully adopt a clinical teacher education Professional Development School (PDS) network approach across the entirety of their teacher preparation programs. Faculty have often been hesitant to commit to such models in light of the demands of institutional expectations of publish or perish. In this book, faculty, researchers, and administrators from academia and from public schools involved in a clinical teacher education PDS network discuss their commitment to collaborative clinical teacher preparation and development, and to inquiry in PDS initiatives in urban schools. Clinical Teacher Education serves as an in-depth analysis of the strengths and challenges of establishing school-university networks in metropolitan environments.Many experienced and noteworthy authors contributed to Clinical Teacher Education. The authors hold various administrative and faculty positions in both university and public school settings.